Analisis Prediksi Kebangkrutan Perusahaan Jasa Sektor Transportasi Di BEI Periode 2019-2021 - Haryani, Sri; Syafei, Jasmina (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
This research aims to determine the prediction and level of accuracy of bankruptcy predictions between the Altman, Zmijewski, Grover, Springate, Fulmer, and Foster models. The sample used in this research is a transportation sector service company listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling technique and obtained a sample size of 21 companies from a population of 47 companies. In this research, the data analysis technique used is descriptive analysis. Based on the results of data analysis, there are differences in results between the Altman, Zmijewski, Grover, Springate, Fulmer, and Foster models in predicting bankruptcy. The accuracy levels obtained from the highest to the lowest respectively were the Grover model (76%), Zmijewski model (71%), Springate model (67%). Fulmer model (57%), Altman model (43%), and Foster model (38%). The Grover model is a bankruptcy prediction model that has the highest accuracy rate of 76%.